2023
DOI: 10.3389/fmicb.2023.1159912
|View full text |Cite
|
Sign up to set email alerts
|

In vivo adaptive antimicrobial resistance in Klebsiella pneumoniae during antibiotic therapy

Abstract: Klebsiella pneumoniae is one of the leading pathogens contributing to antimicrobial resistance. The emergence of carbapenem-resistant K. pneumoniae (CRKP) has put the use of clinical antimicrobial agents in a dilemma. In particular, CRKP exhibiting resistance to ceftazidime/avibactam, tigecycline and colistin have raised great clinical concern, as these are the last-resort antibiotics for the treatment of CRKP infections. Within-host evolution is a survival strategy closely related to the emergence of antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Clonal complex 258 (CC258) is one of the CRKP clones disseminating all over the world 6 . In particular, CRKP exhibiting resistance to colistin and tigecycline have raised important clinical concern, as these are the last‐line drugs for the treatment of these isolates 7 . The worldwide prevalence of colistin‐resistant K. pneumoniae simplified by chromosomal and plasmid‐mediated LPS changes have steadily increased with increased colistin usage for treating CRKP isolates 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal complex 258 (CC258) is one of the CRKP clones disseminating all over the world 6 . In particular, CRKP exhibiting resistance to colistin and tigecycline have raised important clinical concern, as these are the last‐line drugs for the treatment of these isolates 7 . The worldwide prevalence of colistin‐resistant K. pneumoniae simplified by chromosomal and plasmid‐mediated LPS changes have steadily increased with increased colistin usage for treating CRKP isolates 8 .…”
Section: Introductionmentioning
confidence: 99%
“…6 In particular, CRKP exhibiting resistance to colistin and tigecycline have raised important clinical concern, as these are the last-line drugs for the treatment of these isolates. 7 The worldwide prevalence of colistin-resistant K. pneumoniae simplified by chromosomal and plasmid-mediated LPS changes have steadily increased with increased colistin usage for treating CRKP isolates. 8 Colistin-resistant K. pneumoniae infections are increasing in intensive care units, particularly in patients who ultimately depend on vascular catheters for long-term or shortterm use.…”
mentioning
confidence: 99%
“…In our study, we have identified the prior use of carbapenems within 90 days as an independent risk factor for CRKP BSIs. It is possible that the production of carbapenemase and porin deficiency contribute to carbapenem resistance in K. pneumoniae during carbapenem therapy ( 30 ). And clinical retrospective analysis has revealed that previous exposure to carbapenems has been proven to have a significant correlation with the acquisition of CRKP compared to CSKP ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has also unveiled the emergence of ceftazidime/avibactam resistance in clinical strains during antimicrobial treatment, attributed to specific mutations in the bla_KPC gene. 45 …”
Section: The Imperative Of Developing Novel Therapeutic Strategies Fo...mentioning
confidence: 99%